ENHANCE: a comparative prospective longitudinal study of cognitive outcomes after 3 years of hearing aid use in older adults - Sarant, Julia Z.; Busby, Peter A.; Schembri, Adrian J.; Fowler, Christopher; Harris, David C. (Frontiers in Aging Neuroscience, 2024)
Background: With an aging population, prevalence of hearing loss and dementia are increasing rapidly. Hearing loss is currently considered the largest potentially modifiable risk factor for dementia. The effect of hearing interventions on cognitive function should therefore be investigated, as if effective, these may be successfully implemented to modify cognitive outcomes for older adults with hearing loss. Methods: This prospective longitudinal observational cohort study compared outcomes of a convenience sample of prospectively recruited first-time hearing aid users without dementia from an audiology center with those of community-living older adults participating in a large prospective longitudinal cohort study who either did not havewith/without hearing loss and/or use hearing aids. All participants were assessed at baseline, 18 and 36 months using the same measures. Results: Participants were 160 audiology clinic patients (48.8% female; mean age 73.5 years) with mild-severe hearing loss, fitted with hearing aids at baseline, and 102 participants of the Australian Imaging, Biomarkers and Lifestyle Flagship Study of Aging (AIBL) (55.9% female; mean age 74.5 years). 18 and 36-month outcomes of subsets of the first participants to reach these points and complete the cognition assessment to date are compared. Primary comparative analysis showed cognitive stability for the hearing aid group while the AIBL group declined on working memory, visual attention, and psychomotor function. There was a non-significant trend for decline in visual learning for the AIBL group versus no decline for the hearing aid group. The hearing aid group showed significant decline on only 1 subtest and at a significantly slower rate than for the AIBL participants (p<0.05). When education effects on cognitive trajectory were controlled, the HA group still performed significantly better on visual attention and on psychomotor function (lower educated participants only) compared to the AIBL group, but not on working memory or visual learning. Physical activity had no effect on cognitive performance trajectory. Conclusions: Hearing aid users demonstrated significantly better cognitive performance to 3 years post-fitting, suggesting that hearing intervention may delay cognitive decline/dementia onset in older adults. Further studies using appropriate measures of cognition, hearing, and device use, with longer follow-up are required.